Peran Customer Delight Memoderasi Esteem Needs terhadap Niat Beli - Nindiaputri, Cokorda Istri Agung Vera; Sudiksa, Ida Bagus (E-Jurnal Manajemen; Vol 7 No 2 (2018)DO - 10.24843/EJMUNUD.2018.v7.i02.p11, 2018)
The purpose of this study is to analyze the role of customer delight in moderating esteem needs to consumer purchase intentions (study on Guess products). This research was conducted in Bali Province with data analysis technique of Moderation Regression Analysis (MRA). Sample size obtained by using purposive sampling method as much as 100 respondents. Based on the results of the analysis can be stated that the esteem needs and customer delight directly affect the consumer's buying intentions on Guess products. Customer delight proved to moderate the relationship of esteem needs to consumers' buying intentions on Guess products. Recommendations that can be recommended for manufacturers Guess should pay attention to the position and views of consumers will use a Guess product to be an inspiration and improve the esteem needs among the community. Guess must be correct in providing information about the advantages over Guess products so that consumers feel comfortable, confident interested and really Guess as a product that is sought and needed.